2004
DOI: 10.1007/s00441-004-0900-z
|View full text |Cite
|
Sign up to set email alerts
|

The subcommissural organ expresses D2, D3, D4, and D5 dopamine receptors

Abstract: Dopamine receptors have been found in certain populations of non-neuronal cells in the brain, viz., discrete areas of ciliated ependyma and the ependymal cells of the choroid plexus. We have studied the presence of both tyrosine-hydroxylase-immunoreactive nerve fibers and dopamine receptors in the subcommissural organ (SCO), an ependymal brain gland that is located in the roof of the third ventricle and that secretes, into the cerebrospinal fluid, glycoproteins that aggregate to form Reissner's fiber (RF). Ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 76 publications
2
9
0
Order By: Relevance
“…Other studies, using autoradiographic techniques with selective ligands, failed to detect the mu and delta opioid receptors in rat CP brain [25,26], probably due to the lower sensitivity of the methodologies used. The present study also confirmed the presence of other neurotransmitter receptors previously described in the CP [27], such as the dopamine receptors. Again, this emphasizes an active role of the CP as a potential site for modulating response to neurotransmitters, which should be further investigated in the context of mood disorders.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies, using autoradiographic techniques with selective ligands, failed to detect the mu and delta opioid receptors in rat CP brain [25,26], probably due to the lower sensitivity of the methodologies used. The present study also confirmed the presence of other neurotransmitter receptors previously described in the CP [27], such as the dopamine receptors. Again, this emphasizes an active role of the CP as a potential site for modulating response to neurotransmitters, which should be further investigated in the context of mood disorders.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the amphioxus infundibular organ, considered homologous to the vertebrate subcommisural organ (Olsson et al 1994), expresses the AmphiD1/β receptor. Such expression is consistent with the finding of D1-like receptors in the vertebrate subcommisural organ (Tomé et al 2004), and we can then suggest an involvement of the AmphiD1/β receptor in the modulation of chemosensory pathways.…”
Section: Resultssupporting
confidence: 84%
“…A few catecholaminergic fibers also reach the SCO (Tomé et al, 2004). Dopamine receptors (D2, D3, D4 and D5) are present on SCO ependyocytes, but probably respond to CSF-borne dopamine rather than that released from nerve fibers in the SCO (Tomé et al, 2004). The SCO exhibits a dense capillary network running beneath the ependymocytes (Duvernoy and Koritke, 1969).…”
Section: Subcommissural Organ (Sco)mentioning
confidence: 96%
“…Serotonergic fibers from the raphé provide some of this neural input (Møllgård et al, 1978;Bouchard, 1979). A few catecholaminergic fibers also reach the SCO (Tomé et al, 2004). Dopamine receptors (D2, D3, D4 and D5) are present on SCO ependyocytes, but probably respond to CSF-borne dopamine rather than that released from nerve fibers in the SCO (Tomé et al, 2004).…”
Section: Subcommissural Organ (Sco)mentioning
confidence: 97%